The role of awareness media campaigns in spreading health awareness and sports culture among students of the College of Sports Sciences and Physical Activity, King Saud University, Saudi Arabia - Kamal , Dina (Journal of Physical Education, 2025)
The current research aims to identify the role of awareness media campaigns in spreading health awareness and sports culture among students of the College of Sports Sciences and Physical Activity, King Saud University, Saudi Arabia.The researchers used the analytical approach with its steps and procedures through the analysis of previous studies and reference research related to the field of research in order to achieve the objectives of the research. The electronic questionnaire was used. The researchers randomly selected the research sample, which consisted of (503) female students.One of the most important results was that the awareness media campaigns emphasized the nation’s interest in women’s health in general and university students in particular. The media has an effective impact on increasing the health awareness of female students at the College of Sports Sciences and Physical Activity at King Saud University. Media campaigns have a significant impact on improving healthy habits, increasing health awareness, and promoting the concept of prevention. One of the most important recommendations was the need to form a committee to evaluate the awareness messages presented by media campaigns, as well as to use innovative methods in this field. Visual and audio media should commit to the continuity, development and sustainability of awareness media campaigns to spread health awareness and sports culture among the public, and to pay attention to presenting more details. The necessity of paying attention to sports media to familiarize female students with the various sports systems, laws and instructions, focusing on hosting analysts and experts in various health and sports specialties, and distinguished champions and players in various activities and all fields.